Excellent Magnetocaloric Properties near 285 K of Amorphous Fe88Pr6Ce4B2 Ribbon - Xiangjie Liu; Jiameng Yuan; Qiang Wang; Ding Ding; Lei Xia (Metals)
A novel amorphous Fe88Pr6Ce4B2 ribbon with better magnetocaloric properties near 285 K is reported in the present work. The Fe88Pr6Ce4B2 ribbon exhibits a typical second-order ferromagnetic–paramagnetic transition near its Curie temperature (Tc, ~284 K), with a maximum magnetic entropy change (−ΔSmpeak) of ~4.15 J/(kg × K) under 5 T and a maximum adiabatic temperature rise (ΔTad) of ~2.57 K under 5 T, both of which are almost the largest amongst the iron-based metallic glasses with Tc = 285 ± 10 K. The high −ΔSmpeak enables several amorphous hybrids with table-like −ΔSm–T curves to be synthesized by appropriately proportioning the Fe88Pr6Ce4B2 ribbon and other amorphous ribbons with different Tc. The larger average −ΔSm and effective refrigeration capacity, as well as the appropriate temperature range, make the two amorphous hybrids potential candidates for use as refrigerants in household magnetic air conditioners.